A dual caudal-fin miniature robotic fish with an integrated oscillation and jet propulsive mechanism. (27th March 2018) - Liao, Pan; Zhang, Shiwu; Sun, Dong
Abstract: This paper presents the development of a biomimetic robotic fish that uses an integrated oscillation and jet propulsive mechanism to enable good swimming performance for small robotic fish. The designed robotic fish is driven by two caudal fins that flap oppositely, which are equipped in parallel at the fish tail. The propulsive mechanism of dual caudal fins is characterized by using numerical analysis, in which the distance between the two caudal fins is a key factor to the integrated mechanism and plays an important role to swimming performance. This finding has been further verified by experiments performed on a miniature robotic fish prototype with 100 mm length and 30 mm diameter. Experimental results have demonstrated the influence of the distance between the two caudal fins to swimming performance. The designed miniature robotic fish can swim stably and efficiently while exhibiting good motion maneuverability such as turning and braking. The developed robotic fish, with advantages of excellent swimming performance and small size, can be potentially used for monitoring and exploration in the underwater environment.